The smoother extension of the nonlinear ensemble transform filter - Paul Kirchgessner; Julian Tödter; Bodo Ahrens; Lars Nerger (Tellus: Series A, Dynamic Meteorology and Oceanography, 2017)
The recently-proposed nonlinear ensemble transform filter (NETF) is extended to a fixed-lag smoother. The NETF approximates Bayes’ theorem by applying a square root update. The smoother (NETS) is derived and formulated in a joint framework with the filter. The new smoother method is evaluated using the low-dimensional, highly nonlinear Lorenz-96 model and a square-box configuration of the NEMO ocean model, which is nonlinear and has a higher dimensionality. The new smoother is evaluated within the same assimilation framework against the local error subspace transform Kalman filter (LESTKF) and its smoother extension (LESTKS), which are state-of-the-art ensemble square-root Kalman techniques. In the case of the Lorenz-96 model, both the filter NETF and its smoother extension NETS provide lower errors than the LESTKF and LESTKS for sufficiently large ensembles. In addition, the NETS shows a distinct dependence on the smoother lag, which results in a stronger error increase beyond the optimal lag of minimum error. For the experiment using NEMO, the smoothing in the NETS effectively reduces the errors in the state estimates, compared to the filter. For different state variables very similar optimal smoothing lags are found, which allows for a simultaneous tuning of the lag. In comparison to the LESTKS, the smoothing with the NETS yields a smaller relative error reduction with respect to the filter result, and the optimal lag of the NETS is shorter in both experiments. This is explained by the distinct update mechanisms of both filters. The comparison of both experiments shows that the NETS can provide better state estimates with similar smoother lags if the model exhibits a sufficiently high degree of nonlinearity or if the observations are not restricted to be Gaussian with a linear observation operator.